Synergistic Antiplatelet Effect of Ridogrel, a Combined Thromboxane Receptor Antagonist and Thromboxane Synthase Inhibitor, and UDCG-212, a cAMP-Phosphodiesterase Inhibitor - Hoet, B; Arnout, J; Deckmyn, H; Vermylen, J (Thrombosis and Haemostasis, 1993)
Ridogrel, a combined thromboxane receptor antagonist and thromboxane synthase inhibitor (1), inhibits platelet aggregation. Following stimulation with arachidonic acid, cAMP-levels are increased in human platelets preincubated with ridogrel, this is due to the known reorientation of the metabolism of the formed endoperoxides towards adenylate cyclase stimulating prostaglandins.Pretreatment of resting platelets with UDCG-212, a cAMP-phosphodiesterase inhibitor (2), also inhibits platelet aggregation induced by arachidonic acid, concomitant with an increase in cAMP levels, due to an inhibition of its breakdown. Under basal conditions, cAMP also is increased.By combining the two drugs, a more than additive action was observed on platelet aggregation and on both resting and stimulated platelet cAMP content. The appropriate combination may result in a more effective antiplatelet strategy.